Astroglia’s role in synchronized spontaneous neuronal activity: from physiology to pathology - Ammothumkandy, Aswathy; Cayce, Alisha; Shariq, Mohammad; Bonaguidi, Michael A. (Frontiers in Cellular Neuroscience, 2025)
The nervous system relies on a balance of excitatory and inhibitory signals. Aberrant neuronal hyperactivity is a pathological phenotype associated with several neurological disorders, with its most severe effects observed in epilepsy patients. This review explores the literature on spontaneous synchronized neuronal activity, its physiological role, and its aberrant forms in disease. Emphasizing the importance of targeting underlying disease mechanisms beyond traditional neuron-focused therapies, the review delves into the role of astroglia in epilepsy progression. We detail how astroglia transitions from a normal to a pathological state, leading to epileptogenic seizures and cognitive decline. Astroglia activity is correlated with epileptiform activity in both animal models and human tissue, indicating their potential role in seizure induction and modulation. Understanding astroglia’s dual beneficial and detrimental roles could lead to novel treatments for epilepsy and other neurological disorders with aberrant neuronal activity as the underlying disease substrate.